Development of a fatigue life prediction methodology for welded steel semi-trailer components based on a new criterion. (January 2020) - Tello, L.; Castejon, L.; Malon, H.; Valladares, D.; Luque, P.; Mantaras, Daniel A.; Ranz, D.; Cuartero, J.
Highlights: Accurate prediction of the fatigue life of welded steel components used in semi-trailers. Understanding of the structural components and improving the manufacturing processes. This contribution is theoretically and practically relevant. Better dynamic behavior, greater vehicle stability and a lower tendency to overturn. An increase in payload, better vehicle performance, and reduction of maintenance. The criterion considers geometry, base material mechanical properties and TAZ. A methodology is developed to predict the fatigue life in welded joints by the FEM. It was validated through the testing and simulation of an axle bracing subset. Abstract: This paper presents a procedure developed to predict the fatigue life in components made of steel, based on the mechanical properties of the base material and Thermally Affected Zones (TAZs) owing to welding. The fatigue life cycles of the studied components are obtained based on a certain survival probability provided by a Weibull distribution. This procedure is thought to be applied on semi-trailer components, and therefore it is proposed for the steels that are typically used in its manufacturing. A criterion for the adjustment of the exponent and the stress stroke of the fatigue life curve in welded joints is proposed in which the parameters that define the alternating stress versus the number of cycles to failure (S-N) curve are obtained exclusively from the ratio between the base material yield stress of a given steel and the strength of its Thermally Affected Zone. This procedure is especially useful for steels that do not have a complete characterization of their fatigue parameters. These developments are implemented in a subroutine that can be applied in commercial codes based on Finite Element Method (FEM) to obtain a fatigue life prediction. Finally, a numerical-experimental validation of the developed procedure is carried out by means of a semi-trailer axle bracing support fatigue analysis.